A randomized controlled trial of Tai chi for balance, sleep quality and cognitive performance in elderly Vietnamese - Nguyen MH (Dove Medical Press, 2012)
Manh Hung Nguyen, Andreas KruseInstitute of Gerontology, Heidelberg University, Heidelberg, GermanyObjective: To evaluate the effects of Tai chi exercise on balance, sleep quality, and cognitive performance in community-dwelling elderly in Vinh city, Vietnam.Design: A randomized controlled trial.Participants: One hundred two subjects were recruited.Intervention: Subjects were divided randomly into two groups. The Tai chi group was assigned 6 months' Tai chi training. The control group was instructed to maintain their routine daily activities.Outcome measures: The Falls Efficacy Scale (FES), Pittsburgh Sleep Quality Index (PSQI), and Trail Making Test (TMT) were used as primary outcome measures.Results: Participants in the Tai chi group reported significant improvement in TMT (part A) (F [1, 71] = 78.37, P < 0.001) and in TMT (part B), (F [1, 71] = 175.00, P < 0.001) in comparison with the control group. Tai chi participants also reported better scores in FES (F [1, 71] = 96.90, P < 0.001) and in PSQI (F [1,71] = 43.69, P = 0.001) than the control group.Conclusion: Tai chi is beneficial to improve balance, sleep quality, and cognitive performance of the elderly.Keywords: Tai chi, sleep, balance